Regional Cooperation in Asia: Long-term Progress, Recent Retrogression, and the Way Forward - Ramgopal Agarwala; Brahm Prakash (Asian Development Bank (ADB), 2002)
"Despite soft and fragmented regionalism, intraregional flows of trade, labor, and capital grew rapidly in Asia over the last few decades. However, in recent years, there has been retrogression in all the three areas basically associated with the slowdown in growth and departure from the East Asian model in these economies. Major Asian economies are now going through a prolonged slump and suffering from a massive misallocation of its resources, both labor and capital. There is now an urgent need for enhanced institutional efforts for regional cooperation in all the three dimensions mentioned above. The process of liberalization in trade, investment, finance, and labor movements needs to continue at the national as well as international level. However, considerable progress has been made in the area of liberalization in merchandise trade in the region and easy gains have already been made. What is urgently needed now is a program for strengthening the regional financial infrastructure, which would involve a vastly increased role for the Asian Development Bank (ADB) in resource transfer within the region and establishment of an "Asian Reserve Bank" (ARB) for greater stability in exchange rates, greater financial security, and greater resource mobilization in the region."
hdl:11540/1936
Keywords: 330; Regionale Wirtschaftsintegration; Regionale Wirtschaftsintegration; Internationale Faktormobilität; Handelsliberalisierung; Geldpolitik; Asien